2006
DOI: 10.1108/14635770610644547
|View full text |Cite
|
Sign up to set email alerts
|

Achieving business excellence through synchronous supply in the automotive sector

Abstract: Purpose -To provide the reader with an appreciation of the present trends in the UK automotive supply industry as they affect the first and second tier supply chain and aims to give researchers an insight into the complex interaction between suppliers and their customers. Design/methodology/approach -Literature review which is divided into the sub-sections of strategy, structure, processes and co-ordination required within the manufacturing environment, to identify the influence of synchronous supply as it aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Companies must regularly perform an assessment to their internal business activities to identify the aspects of business priority, product structure (which may involve an alliance to support certain production activities), human capital and management, and investment (Errin, 2004;Silveira and Cagliano, 2006). The main advantage of self-assessment is to oversee the major challenges for SMEs which are related to speed of technology adoption (Kleindl, 2000), human resource development (Hudson et al, 2001), new product development (Sonia and Francisca, 2005) and finally managing its supply competitors and other organisations such as consulting firms and research centres (Soh and Roberts, 2005;Bennett and O'Kane, 2006). The case studies below illustrate that when the internal activities are not assessed and corrected, it can result in a myopic and short-term strategy, and eventually failure.…”
Section: The Case Studiesmentioning
confidence: 99%
“…Companies must regularly perform an assessment to their internal business activities to identify the aspects of business priority, product structure (which may involve an alliance to support certain production activities), human capital and management, and investment (Errin, 2004;Silveira and Cagliano, 2006). The main advantage of self-assessment is to oversee the major challenges for SMEs which are related to speed of technology adoption (Kleindl, 2000), human resource development (Hudson et al, 2001), new product development (Sonia and Francisca, 2005) and finally managing its supply competitors and other organisations such as consulting firms and research centres (Soh and Roberts, 2005;Bennett and O'Kane, 2006). The case studies below illustrate that when the internal activities are not assessed and corrected, it can result in a myopic and short-term strategy, and eventually failure.…”
Section: The Case Studiesmentioning
confidence: 99%
“…Using the automotive industry as the example, a supplier would deliver the exact variation of product matching each individual car on the customer's production line. Synchronous supply therefore necessitates superior planning and control to enforce 100% customer requirements (Bennett and O'Kane, 2006;Bennett and Klug, 2012).…”
Section: Synchronous and Sequence Supplymentioning
confidence: 99%
“…The VMUK plant is seen as one of the most efficient vehicle manufacturing plants in Europe and also a world class manufacturer comparable with manufacturing facilities in Japan (Bennett and O'Kane, 2006). After interviewing the respondent at VMUK the authors' feel their standards could be seen as a benchmark for their suppliers to work towards;…”
Section: Figure 3 Herementioning
confidence: 99%
“…Research has shown that collaborative approaches involving suppliers significantly contribute to improved product quality, shorter lead times and a higher responsiveness of the supply chain at lower costs and increased customer satisfaction levels (Bennett and O'Kane 2006; Tummala, Phillips and Johnson 2006; Humphreys, Huang et al 2007). In the automotive industry, which is characterized by a high degree of value added by suppliers in manufacturing as well as in the engineering of car components (Tiemann, Scholz and Thies 2000; Quesada, Syamil and Doll 2006; Wagner, Bode and Koziol 2009), suppliers are integrated in both joint production planning (Fawcett, Osterhaus et al 2003; Bennett and O'Kane 2006) and joint product development processes (Takeishi 2001; Bates, Holweg, et al 2007; Binder, Gust and Clegg 2007; Holweg and Pil 2007). These practices aim at realizing competitiveness at the company and supply chain levels in terms of costs, quality, innovation, and product development as well as production lead times (Becker and Zirpoli 2003; Doran 2003, 2004; Binder et al 2007).…”
Section: Introductionmentioning
confidence: 99%